Innovation-investment platform of complex ensuring the economic security of enterprises of agrarian industry - Vinichenko, Igor; Вініченко, Ігор Іванович; Honcharenko, Oksana; Гончаренко, Оксана Володимирівна; Khalatur, Svitlana; Халатур, Світлана Миколаївна; Sitkovska, Alla; Сітковська, Алла Олександрівна; Prus, Yurii; Прус, Юрій; Korchahina, Vita; Корчахіна, Віта (My University, 2020)
The article deals with theoretical and methodological aspects of innovation and investment development of agrarian enterprises in the symbiosis of determinants of ensuring the economic security of meso- and micro levels. Ensuring the economic security of an agricultural enterprise is presented as a necessary component in its sustainable development, as well as in achieving its well-being. The purpose of the article was search of a comprehensive approach to balancing the directions of efficient activity of agrarian enterprises of innovative type, preserving a favorable institutional environment of economic security of the agrarian industry, with observance of rational parameters of using financial and resource capital, improving the quality of agricultural products in the trend of dynamic growth of investment activity is proved. The criterion and block diagram of the balance of the cycles of innovation and investment development in the complex maintenance of economic security of the enterprise of the agrarian industry have been developed, with the aim of achieving uniformity of the magnitude of the “net present value of investment costs” by the branch of activity of economic entities. Practical significance of the article lies in the fact that the proposed approach allows to determine the proportional distribution of investments in the innovative development of agrarian enterprises, taking into account the speed of change in the profitability of agricultural products in a certain cycle of activity. У статті розглядаються теоретичні та методологічні аспекти інноваційно-інвестиційного розвитку аграрних підприємств у симбіозі детермінант забезпечення економічної безпеки мезо- та мікрорівнів. Забезпечення економічної безпеки сільськогосподарського підприємства представляється як необхідна складова його стійкого розвитку, а також досягнення його добробуту. Метою статті був пошук комплексного підходу до збалансування напрямків ефективної діяльності аграрних підприємств інноваційного типу, збереження сприятливого інституційного середовища економічної безпеки аграрної галузі, з дотриманням раціональних параметрів використання фінансового та ресурсного капіталу, доведено підвищення якості сільськогосподарської продукції в тенденції динамічного зростання інвестиційної активності. Розроблено критерій та блок-схему збалансованості циклів інноваційно-інвестиційного розвитку в комплексному забезпеченні економічної безпеки підприємства аграрної галузі з метою досягнення однаковості величини “чистої теперішньої вартості інвестиційні витрати »за галуззю діяльності суб’єктів господарювання. Практичне значення статті полягає в тому, що запропонований підхід дозволяє визначити пропорційний розподіл інвестицій в інноваційний розвиток аграрних підприємств з урахуванням швидкості зміни прибутковості сільськогосподарської продукції в певному циклі діяльності. The article deals with theoretical and methodological aspects of innovation and investment development of agrarian enterprises in the symbiosis of determinants of ensuring the economic security of meso- and micro levels. Ensuring the economic security of an agricultural enterprise is presented as a necessary component in its sustainable development, as well as in achieving its well-being. The purpose of the article was search of a comprehensive approach to balancing the directions of efficient activity of agrarian enterprises of innovative type, preserving a favorable institutional environment of economic security of the agrarian industry, with observance of rational parameters of using financial and resource capital, improving the quality of agricultural products in the trend of dynamic growth of investment activity is proved. The criterion and block diagram of the balance of the cycles of innovation and investment development in the complex maintenance of economic security of the enterprise of the agrarian industry have been developed, with the aim of achieving uniformity of the magnitude of the “net present value of investment costs” by the branch of activity of economic entities. Practical significance of the article lies in the fact that the proposed approach allows to determine the proportional distribution of investments in the innovative development of agrarian enterprises, taking into account the speed of change in the profitability of agricultural products in a certain cycle of activity.
Інноваційно-інвестиційна платформа комплексу, що забезпечує економічну безпеку підприємств аграрної галузі
Keywords: agrarian enterprises; аграрні підприємства; agrarian industry; аграрна промисловість; economic security; економічна безпека; innovation-investment development; інноваційно-інвестиційний розвиток; multi-agro-cluster; мульти-агрокластер